2019
DOI: 10.5114/cipp.2019.89168
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy as a mediator of the relationship between meaning in life and subjective well-being in cardiac patients

Abstract: The theoretical framework and empirical data suggest that the relationship between meaning in life and well-being might be mediated by self-efficacy. Based on the cognitive-affective processing system (CAPS), self-concordance model and empirical data, we assume that self-efficacy might also act as a mediator between meaning in life and subjective well-being in cardiac patients. participants and procedure This study was conducted in cardiology units in Poland. Patients who met the inclusion/exclusion criteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 52 publications
0
13
0
8
Order By: Relevance
“…As explained, various studies show a positive correlation between subjective well-being and other variables such as self-concept, and self-efficacy ( Huebner, 1991 ; Harter, 1998 ; McCullough et al, 2000 ; Luján, 2002 ; Gutiérrez and Gonçalves, 2013 ). Literature has also suggested that self-efficacy may mediate the relations between subjective well-being and other constructs such as meaning in life, life satisfaction and self-concept ( Krok and Gerymski, 2019 ). In the case of native-born students, the results controlled by gender assume a direct relationship between academic self-concept and subjective well-being; however, general self-efficacy also presents a mediational role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As explained, various studies show a positive correlation between subjective well-being and other variables such as self-concept, and self-efficacy ( Huebner, 1991 ; Harter, 1998 ; McCullough et al, 2000 ; Luján, 2002 ; Gutiérrez and Gonçalves, 2013 ). Literature has also suggested that self-efficacy may mediate the relations between subjective well-being and other constructs such as meaning in life, life satisfaction and self-concept ( Krok and Gerymski, 2019 ). In the case of native-born students, the results controlled by gender assume a direct relationship between academic self-concept and subjective well-being; however, general self-efficacy also presents a mediational role.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lack of studies of this nature in Chile. In the same line, literature has reported that self-efficacy would play a mediational role between subjective well-being and other constructs such as meaning in life, life satisfaction and even personality traits such as extraversion and openness ( Krok and Gerymski, 2019 ). To the best of our knowledge the relations between self-concept and subjective well-being have been widely described but no contribution has been made regarding the mediational role of self-efficacy between these two constructs (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 97%
“…According to the research of Krok and Gerymski (2019), the sense of self-efficacy is also a partial mediator (positive influence) in the relationship between the meaning of life and life satisfaction. Studies carried out by Słupiński and Kałużny (2016) indicate that a sense of self-efficacy and a sense of location of control can have an impact on the choice of style of coping with a difficult situation -the stronger the sense of self-responsibility, the less willingness to react with anxiety and applying failure protection strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers noted a mediating role of self-efficacy between meaning in life and subjective well-being [ 35 , 36 ]. We wanted to check whether we would be able to observe the same relationship in the case of psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…People with a low level of self-efficacy may have difficulty perceiving their life as understandable, and thus have a lower sense of well-being [34]. Researchers point to the mediating role of self-efficacy between meaning in life and well-being; however, previous studies have focused on the hedonic, not the eudemonic, approach [35,36]. Due to the relationships between meaning in life, well-being, and self-efficacy, as well as due to the fact that this study is a designed intervention focused on difficult and stressful everyday events, we decided that it is worth considering self-efficacy in our research.…”
Section: Introductionmentioning
confidence: 99%